Nagari Adat di Minangkabau Dalam Tinjuan Sejarah - Refni Yulia; Livia Ersi (Bakaba : Jurnal Sejarah, Kebudayaan dan Kependidikan, 2022)
Nagari Adat in Minangkabau are autonomous nagari and part of the lowest nagari governance system in West Sumatra. The naming of adat nagari in West Sumatra is more for the sake of tourism, so that some nagari that have tourism potential were developed into adat nagari and promoted on a district and provincial basis. So that the first 4 traditional villages were chosen, namely, the Indudur angari, the Seribu Gadang Nagari, Pariyangan Nagari, and Jawi-Jawi villages. The four nagari have become national tourist destinations and have been visited by domestic and foreign tourists and were recorded in the tourist calendar in West Sumatra. The development of adat nagari ultimately spurred other nagari to develop their potential in their adat and tourism.